3D finite element analysis for varicose vein therapy by using microwave ablation - Prasantamrongsiri, S.; Phasukkit, P.; Pintavirooj, C.; Tungjitkusolmun, S.; Sanpanich, A. (My University, 2012)
This paper presents three-dimensional finite element method for analyze a varicose vein microwave ablation. Varicose vein can contract by using heat from microwave ablation. Because of varicose vein patients have leg pain from long time standing, and do a lot of activities. Symptoms have influenced the daily life of patients. We study method for varicose vein therapy by using microwave ablation. Because of this method is easy to use for varicose vein therapy. In this research work, we propose simulation varicose vein that varicose vein is inserted with antenna into blood vessel. Simulation method delivers microwave to antenna inserted in varicose vein. For this reason, varicose vein is contract. Finite element analysis can apply in treatment planning and show temperature distribution and specific absorption rate (SAR) distribution for contract of varicose vein characteristic by using microwave therapy. And the doctor can be use the data for treat in future. ©2012 IEEE.
Keywords: Antenna; Finite element; Microwave ablation; Varicose vein